BIOGRAFIA ZAWODOWA JAKO ŹRÓDŁO WIEDZY – AUTOBIOGRAFICZNE REFLEKSJE EMERYTOWANYCH NAUCZYCIELEK JĘZYKA OBCEGO - Werbińska, Dorota (Neofilolog, 2019)
This article reports a qualitative research project focused on examining the professional biographies of four post-service Polish teachers of foreign languages. The main objective was to find out what experiences in their professional biographies the participants perceived as the most critical, and to see if those memories were roughly similar in the participants’ accounts. Following Karol Wojtyła’s (1994) anthropological views connected with a person’s structure and their dynamism, the study discusses the subjects’ experiences relating to teacher reactivity, emotivity and agency against the socio-political background of Poland in the period before and after political transformation.